O pacto pela vida no estado de Pernambuco: informação, política e poder. - Silva, Edilene Maria da (2016)
The study on information management of Pacto pela Vida (Pact for Life) of Pernambuco state shows the relationship among information, politics and power. Monitoring systematics, originated from the management model by results, Todos por Pernambuco (All for Pernambuco), requires the intensive use of accurate and relevant information. For this purpose, the government created structural, instrumental and political conditions so that information becomes one of the elements of support for the evaluation of public policies and decision-making. These assumptions lead to the thesis that the policy and management by results interfere in the information flow that subsidizes the public administration, changing the exercise of power of the tactical level actors who develop informational practices, invisible or nonexistent, in the predominantly bureaucratic administration. Theoretically, the study relies on the theoretical pluralism of information described by Braman (1989; 2009), in which several understandings of information can be associated with different stages of political decision-making. Likewise, the study uses four power exercise demonstrations: instrumental, structural, symbolic and informational, studied by the mentioned author. The objective focuses on analyzing how the political strategy and the public administration change of Pernambuco state government alter the power of the actors involved in Pacto pela Vida (Pact for Life) through the intensive use of information. The methodological procedures are composed of content analysis of interviews with governmental actors of the strategic, tactical and operational levels and the Pacto pela Vida (Pact for Life) legislation; for this purpose, NVivo software was used. The documentation and interviews were examined through the content analysis and guided by the theoretical assumption referring to information, power and politics, which constituted categories and subcategories established a priori and regrouped in compliance with Bardin (2009) who establishes the categorization as the classification of constituent elements of a set by differentiation and then by regrouping, according to gender with predefined criteria. Visits were also carried out in the Management Center by Results, Statistical and Criminal Analysis Management and in judicial district stations and neighborhood police stations to make direct observation of informational practices undertaken in these places. It can be concluded that information is in the genesis of the monitoring and evaluation process as well as in the basis of instrumental, structural, symbolic and informational powers. Information is used to exercise control over individuals, institutions, processes, results, shaping behaviors, creating and spreading ideas and images; in short, creating in the governmental and non-governmental actors´ minds confidence of the benefits regarding the new model for conducting the State. The policy and management by results interfere in the information flow that subsidizes the public administration and alter the exercise of power of the tactical level actors who develop informational practices, invisible or nonexistent, in the bureaucratic administration. Thus, the thesis was confirmed. Moreover, it is recognized that the problem of information in Brazil is eminently political, once it depends on the Brazilian government's decision to make the information a resource for management and a basic tool of accountability and social control.